2013
DOI: 10.1093/her/cyt054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of targeted health promotion on cardiovascular knowledge among American Indians and Alaska Natives

Abstract: The National Heart, Lung, and Blood Institute developed the Honoring the Gift of Heart Health (HGHH) curriculum to promote cardiovascular knowledge and heart-healthy lifestyles among American Indians and Alaska Natives (AI/ANs). Using data from a small randomized trial designed to reduce diabetes and cardiovascular disease (CVD) risk among overweight/obese AI/ANs, we evaluated the impact of an adapted HGHH curriculum on cardiovascular knowledge. We also assessed whether the curriculum was effective across leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
2
12
0
1
Order By: Relevance
“…Culturally appropriate interventions have previously demonstrated an association with improved health knowledge about diabetes and CVD. 45 46 Counselling that incorporates successful adult education techniques such as reinforcement and feedback, teachback, assessing and confirming patients’ understandings, and patient-tailored information all build health literacy. 44 47 Research involving pill cards for health literacy has tended to focus on pill cards as a management tool for low health literate populations as opposed to assessing how they build health literacy skills and capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culturally appropriate interventions have previously demonstrated an association with improved health knowledge about diabetes and CVD. 45 46 Counselling that incorporates successful adult education techniques such as reinforcement and feedback, teachback, assessing and confirming patients’ understandings, and patient-tailored information all build health literacy. 44 47 Research involving pill cards for health literacy has tended to focus on pill cards as a management tool for low health literate populations as opposed to assessing how they build health literacy skills and capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention trials located within Indigenous communities are rare. Brega et al 45 found that the ‘Honouring the Gift of Heart Health’ intervention increased knowledge about CVD, symptoms associated with MI and stroke, and CVD risk factor control, in both high and low health literacy groups of American Indian and Alaska Native peoples. 45 The current study and that of Brega et al demonstrate that appropriately designed interventions can be successfully implemented in Indigenous communities.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, AI/AN knowledge of heart attack and stroke symptoms was more limited than that of the general population [ 91 ]. Although they understand the risk of obesity and importance of physical inactivity in CVD development, they are unable to tell what blood pressure values would be considered high [ 91 , 92 ]. The National Heart, Lung, and Blood Institute (NHLBI) developed the Honoring the Gift of Heart Health (HGHH) curriculum to focus on improving the HL level of AI/AN communities.…”
Section: Prevention Of Dm and Cvd In The Ai/an Populationmentioning
confidence: 99%
“…The National Heart, Lung, and Blood Institute (NHLBI) developed the Honoring the Gift of Heart Health (HGHH) curriculum to focus on improving the HL level of AI/AN communities. Improvements in HL levels, including heart attack knowledge, stroke, and general CVD knowledge, have been observed in HGHH curriculum participants [ 92 ].…”
Section: Prevention Of Dm and Cvd In The Ai/an Populationmentioning
confidence: 99%
“…Evidence from the United States (2) and Canada (3) confirms that indigenous people have up to twice the risk of stroke, compared with nonindigenous people; because of a higher prevalence of diabetes, they also have a higher risk of experiencing stroke at younger ages (4,5). Although culturally tailored cardiovascular disease prevention programs have been developed for indigenous communities, such as the Honoring the Gift of Heart Health Curriculum (6), Montana Cardiovascular Health Program (7), or In Our Voice Curriculum for American Indian Students (8), evaluations indicate that such programs often do not produce expected improvements in stroke awareness, unless culturally specific and community-relevant content is offered.…”
Section: Introductionmentioning
confidence: 99%